Active and passive organic carbon fluxes during a bloom in the Southern Ocean (South Georgia) - William Major; Sarah L. C. Giering; Joanna Ainsworth; Anna Belcher; Sabena Blackbird; Martin Bridger; Nathan Briggs; Filipa Carvalho; Louis Clément; Kathryn Cook; Cynthia Dumousseaud; Benoit Espinola; et al. (Scientific Data)
Abstract The Controls Over Mesopelagic Interior Carbon Storage (COMICS) cruise DY086 took place aboard the RRS Discovery in the South Atlantic during November and December, 2017. Physical, chemical, biogeochemical and biological data were collected during three visits to ocean observatory station P3, off the coast of South Georgia, during an austral spring bloom. A diverse range of equipment including CTD-rosette, Acoustic Doppler Current Profiler (ADCP), net deployments, marine snow catchers (MSCs), Stand Alone Pump System (SAPS) and PELAGRA Sediment Traps were used to produce a comprehensive, high-quality dataset. The data can provide excellent insight into regional biological carbon pump (BCP) processes; it is recommended for use by observational scientists and modellers to enhance understanding of ecosystem interactions relating to mesopelagic carbon storage.